2013
DOI: 10.1007/978-1-4614-5833-3
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological Changes and Estuarine Dynamics

Abstract: The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific statement, that such names are exempt from the relevant protective laws and regulations and therefore free for general use. While the advice and information in this book are believed to be true and accurate at the date of publication, neither the authors nor the editors nor the publisher can accept any legal responsibility for any errors or omissions that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 1 publication
0
62
0
1
Order By: Relevance
“…Additional research is needed to elucidate the relative importance of different kinds of freshwater inputs (e.g., the relative importance of local rainfall in comparison to watershedbased freshwater inflows), as well as the influence of landscape position (e.g., tidal position, geomorphology, hydrologic connectivity). Such investigations would help inform policy discussions regarding the allocation of freshwater flows to support estuarine ecosystem goods and services in dryland landscapes (e.g., Alber 2002, Montagna et al 2013. Collectively, our analyses highlight the importance of evaluating the effects of macroclimatic drivers (e.g., rainfall, temperature) within future-focused coastal wetland management plans and modeling efforts, especially along the Gulf of Mexico coast where climate-driven ecological transitions and thresholds are abundant.…”
Section: Discussionmentioning
confidence: 95%
“…Additional research is needed to elucidate the relative importance of different kinds of freshwater inputs (e.g., the relative importance of local rainfall in comparison to watershedbased freshwater inflows), as well as the influence of landscape position (e.g., tidal position, geomorphology, hydrologic connectivity). Such investigations would help inform policy discussions regarding the allocation of freshwater flows to support estuarine ecosystem goods and services in dryland landscapes (e.g., Alber 2002, Montagna et al 2013. Collectively, our analyses highlight the importance of evaluating the effects of macroclimatic drivers (e.g., rainfall, temperature) within future-focused coastal wetland management plans and modeling efforts, especially along the Gulf of Mexico coast where climate-driven ecological transitions and thresholds are abundant.…”
Section: Discussionmentioning
confidence: 95%
“…This paper highlights the relationship between water quality variables, benthic macrofauna and their use as food resources by a carnivorous fish species. Although many studies have revealed connections between water quality variables and benthic macrofauna (Montagna et al ., ), this study emphasizes the need for more integrated assessments of food‐web functioning when studying effects of changes in water quality. Holistic approaches such as these can serve as an important component toward conservation and sustainable fisheries management (Ludwig et al ., ) and improved prediction of estuarine response to increasing climatic variability (Bailey & van de Pol, ; Wetz & Yoskowitz, ).…”
Section: Discussionmentioning
confidence: 99%
“…Relatively little freshwater enters this estuary from the Nueces River and Oso Creek. Low amounts of freshwater inflows coupled with high rates of evaporation cause the estuary to become hyper-saline for much of the year (Montagna et al, 2012).…”
Section: Study Area Climate and Sedimentary Processesmentioning
confidence: 99%